Lady in the lake [compact disc, unabridged] : a novel - Lippman, Laura, 1959- (HarperAudio, 2019)
A divorced reporter in racially torn 1966 Baltimore triggers unanticipated consequences for vulnerable community members while investigating the murder of an African-American party girl.